Redesign arabic calligraphy outline by using Bezier, Wang-Ball and Said-Ball curves / Noorehan Awang, Fatin Najihah Ghazali and Siti Sarah Zainuddin - Awang, Noorehan; Ghazali, Fatin Najihah; Zainuddin, Siti Sarah (Universiti Teknologi MARA, Perak, 2022)
Arabic calligraphy was one of the art phenomena. This research suggests using Bezier curves, Wang Ball curves, and Said-Ball curves to improve Arabic calligraphy. Our goal in calligraphy is to achieve a smooth beautifying contour of a character. The calligraphy outline, which was largely Arabic, was frequently applied in Bezier curve degrees two and three. As a result, the degree elevation for each curve was increased until it reached degree four, allowing for greater Bezier curve study. This paper presents the comparisons between those three curves by using the Arabic calligraphy "Aamin" as the subject. Curve fitting, curve manipulation, mixing, and merging of curves were all examples of how Bezier curves were employed in Computer Aided Design. Ball curves, also known as a generalized ball basis, are a type of curve that has arbitrary even and odd degrees. There were two types of generalized ball curves: Wang-ball curves and Said-ball curves, each with their own special position parameter. The best curves of the Bezier, Wang-Ball, and Said-Ball curves were combined to create "Aamin" calligraphy. All of the results were programmed into the MATLAB software and graphed. For the redesign "Aamin" calligraphy Bezier curve computes the best time compared to Wang-Ball and Said-Ball curve. The computation time in MATLAB software for the degree 2, degree 3 and degree 4 are 1.48 seconds, 1.52 seconds and 2.50 seconds respectively. The higher the degree elevation, the longer the computation time to generate "Aamin" calligraphy, according to these findings. This research provides the fundamental design and empirical findings in the process of improving the production of computerized Arabic calligraphy.